2017
DOI: 10.7554/elife.31683
|View full text |Cite
|
Sign up to set email alerts
|

Transcription-factor-dependent enhancer transcription defines a gene regulatory network for cardiac rhythm

Abstract: The noncoding genome is pervasively transcribed. Noncoding RNAs (ncRNAs) generated from enhancers have been proposed as a general facet of enhancer function and some have been shown to be required for enhancer activity. Here we examine the transcription-factor-(TF)-dependence of ncRNA expression to define enhancers and enhancer-associated ncRNAs that are involved in a TF-dependent regulatory network. TBX5, a cardiac TF, regulates a network of cardiac channel genes to maintain cardiac rhythm. We deep sequenced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
73
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(77 citation statements)
references
References 45 publications
(80 reference statements)
4
73
0
Order By: Relevance
“…RT-PCR experiments have shown that several eRNAs are intergenic chromatin enriched RNAs (icheRNA) [7]. Werner et al also showed that protein-coding genes proximal to icheRNA have higher expression levels than those near to other expressed lncRNA, suggesting that icheRNA could predict cis-gene transcription [4,5].…”
Section: Icherna Positively Correlate With Adjacent Genes In Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…RT-PCR experiments have shown that several eRNAs are intergenic chromatin enriched RNAs (icheRNA) [7]. Werner et al also showed that protein-coding genes proximal to icheRNA have higher expression levels than those near to other expressed lncRNA, suggesting that icheRNA could predict cis-gene transcription [4,5].…”
Section: Icherna Positively Correlate With Adjacent Genes In Expressionmentioning
confidence: 99%
“…Among these nuclear lncRNAs, chromatin-associated lncRNA (cheRNA) processes gene-regulatory roles [4][5][6]. In our recent studies, cheRNA promotes essential gene-enhancer contacts and is associated with transcript factor-dependent lncRNA [5,7]. However, a robust analytic pipeline for cheRNA as a group of functional nuclear RNAs has not been performed.…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of literature indicates that noncoding RNAs (ncRNAs) are transcribed from active CREs. The function of these transcripts and their role in gene regulation is an area of active research 1,710 . We previously demonstrated that differential enhancer transcription can be used to define a gene regulatory network (GRN) 1 .…”
Section: Introductionmentioning
confidence: 99%
“…The function of these transcripts and their role in gene regulation is an area of active research 1,710 . We previously demonstrated that differential enhancer transcription can be used to define a gene regulatory network (GRN) 1 . We identified ncRNAs whose expression was dependent on the cardiac transcription factor TBX5 1 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation